NEW METHOD TO IMPROVE THERMAL-STABILITY IN THE INTERFACE OF SILICON AND TUNGSTEN BY THE INTERPOSITION OF PLASMA-DEPOSITED TUNGSTEN NITRIDE THIN-FILM - LEE, CW; KIM, YT; LEE, JY (AMER INST PHYSICS, 1994)
Thermally stable tungsten nitride/tungsten bilayer has been proposed for the application of metallization. This bilayer is sequentially formed by plasma enhanced chemical vapor deposition without breaking vacuum. The Rutherford backscattering spectrometry and cross-sectional transmission electron microscopy reveal that the interaction between the W and Si substrate can be prevented by interposing a 800-Angstrom-thick W67N33 layer. The W67N33/W bilayer maintains the integrity of the interface during annealing at 850 degrees C for 30 min without the formation of Si2W and interdiffusion phenomena. Sheet resistivity of the W67N33/W bilayer is gradually decreased from 17 to 12 mu Omega cm at annealing temperatures up to 850 degrees C.